FAKTOR YANG MELATARBELAKANGI ORANG DEWASA MENGIKUTI PENDIDIKAN KESETARAAN - Riyanti, Nita; Agustia, Zahra; Muslim, Muhammad Nur; Laksono, Bayu Adi (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Everyone's educational needs are of course different. In the context of adults who do not continue their education at a formal level, of course the equal education program becomes a bridge as an aspect of meeting their needs. As is the case, PKBM Harapan Baru is a bridge in meeting the learning needs of its residents. PKBM Harapan Baru provides several levels of equality packages, namely Package A, Package B and Package C, which aim to help students obtain knowledge, skills and diplomas. In February, research was carried out at PKBM Harapan Baru for a period of three weeks with the aim of finding out and understanding the factors that form the background of adults participating in the equality package education program. This research involves several stages, namely: problem identification stage, planning stage, implementation stage, and evaluation stage. Education provided to adults or learning citizens aims to equip adults with knowledge and skills to meet their needs.